A critical analysis of the experience of mumpreneurs: a study based on tourism industry in Sri Lanka. (13th January 2023) - Ranwala, Ranwala S.; Surangi, H.A.K.N.S.
Work-life balance and its implications for the success of female entrepreneurs in Asian countries is a relatively neglected topic in the scholarly literature. Therefore, the study explores the work-life balance experience of mumpreneurs in the Sri Lankan tourism industry. This qualitative study used the narrative approach, and ten mumpreneurs were selected and interviewed by following the purposive sampling method. Thematic analysis was used to analyse the collected data. Findings revealed that social, environmental and individual factors are the main themes when choosing entrepreneurship as a career option, and mumpreneurs have issues satisfying both family and business demands. Mumpreneurs use coping strategies such as networking, planning the day, managing the time, doing business at home and doing the business only for survival. The present study enriches the understanding of the behaviours of mumpreneurs in the tourism industry and contributes to the literature by introducing a new model of mumpreneurs' experience.